Cytarabine‐induced TNFα promotes the expansion and suppressive functions of myeloid‐derived suppressor cells in acute myeloid leukaemia. (20th March 2022) - Bai, Hua; Peng, Yuhui; Li, Yi; Duan, Juanjuan; Fu, Wenli; Liang, Xinming; Yu, Wenfeng; Zhang, Qifang
Abstract: Acute myeloid leukaemia (AML) is very common haematopoietic malignancies with poor prognosis. Chemotherapy is still a mainstay therapy for AML patients. AML microenvironment plays critical roles in therapy response. However, the role of chemotherapy in AML microenvironment is poorly understood. In this study, we report that cytarabine (AraC)‐triggered TNFα from AML cells expanded myeloid‐derived suppressor cells (MDSCs) and enhanced MDSC functions and survival through activating IL‐6/STAT3 and NFκB pathways. Blockade of TNFα in conditioned medium‐derived AraC‐treated AML cells (AraC_CM) impaired MDSC expansion and functions, reduced IL‐6 secretion and the level of activated STAT3. Inhibiting IL6 or STAT3 abrogated AraC_CM‐mediated MDSC suppressive function. Additionally, inhibiting TNFα also impaired AraC_CM‐mediated NFκB activation. Blocking NFκB activation reduced MDSC viability induced by AraC_CM. Together, these results provided a role of AraC‐induced TNFα in MDSC expansion and functions and suggest that targeting TNFα may benefit AML patients to current anticancer strategies by blocking MDSC‐mediated immunosuppression.